Synthesis of New Schiff’s Bases Derived from 4-Phthalimidyl Acetophenone - Ali, Rana Abid (Al-Nahrain Journal of Science, 2018)
Eight new Schiff’s bases were prepared in three steps. The first step includes synthesis of phthalamic acid from the reaction between phthalic anhydride with p-amino acetophenone which in turn fused in the second step to form the corresponding phthalimide. The third step involved condensation of the prepared phthalimide with different primary aromatic amines to form new Schiff’s bases. These compounds were characterized by FT-IR, 1H-NMR and 13C-NMR spectroscopy. Most of the synthesized compounds have been screened for their antimicrobial activities by using agar cup plate method against two types of bacteria .The results showed that the new Schiff’s bases exhibit good to moderate antibacterial activity.